Implications of Anti-Bullying Learning Through Anti-Bullying Seminars at SDN 02 Patemon - Khadafi Wijaya; Mustakimah Mustakimah (Universitas Palangka Raya, 2024)
Character is important in the progress of the nation and state. In advancing the Golden Indonesia, a strong character of the next generation is needed. With prevention through anti-bullying, the character of the nation’s successors can be directed to a better path. Bullying is a behaviour that can make people around feel pain or pain either verbally, physically, or mentally. This research uses a descriptive research method that displays the results of the analysis of the activities carried out. The implication of improving the nation’s character and avoiding bullying characters is the anti-bullying socialization with the theme “bullying is a wound not a joke